Geophysical investigation of the down-dip extension of the Lombador massive sulphide deposit, Neves-Corvo, Portugal - Dias, Pedro (2021)
ABSTRACT: The 150 Mt Lombador massive sulphide deposit is one of the seven known deposits of the Neves-Corvo mine. The deposit dips approximately 30º–35º to the NE and is open down dip, with current exploitation reaching down at 1 km depth. To investigate the possible downwards continuation of the deposit, a 1D constrained inversion of time-domain electromagnetic (TEM) ground loop data was conducted, followed by 3D electromagnetic (EM) forward modeling and a constrained 3D gravimetric inversion over the same area. To perform the EM and gravity modeling/inversion, a 3D geologic model was built using a density database comprising of approximately 300 drill-holes, and an electrical conductivity database with measurements from resistivity surveys and 1D inversion of the TEM data. The EM modeling shows that the Neves Forma tion shales are a regional conductive layer extending down to approximately 1.6 km depth in the Lombador area. This layer, often topped by massive sulphides, has an average density of 2.83 g/cm3 , whereas stockwork and massive sulphide reach on average 3.1 g/cm3 and 4.5 g/cm3 , respectively. The 3D constrained gravity inversion results do not support the hypothesis of the presence of massive sulphides located in the down-dip direction of the Lombador deposit in the immediate vicinity of the known deposit. The lack of spatial resolution of the gravity grid, the study area limited size and the lack of information from within the basement suggest further studies are required to confrm the presence and amount of stockwork mineraliza tion down-dip the Lombador deposit inside the Neves-Formation or the Phyllite-Quartzite basement.